The impact of job stress on job satisfaction and turnover intentions among bank employees during the COVID-19 pandemic - Lin, Mei-Hui; Yen, Ya-Hui; Chuang, Tsai-Fu; Yang, Ping-Sen; Chuang, Ming-Da (Frontiers in Psychology, 2024)
Objective The main objective of this study is to explore the relationships among job stress, job satisfaction, and turnover intentions among bank employees during the COVID-19 pandemic, with a focus on variations across different demographic characteristics. Methods A cross-sectional design was employed, and data were collected from 501 bank employees using the Job Stress Questionnaire (JSQ), the Simplified Minnesota Satisfaction Questionnaire (MSQ), and the Intention to Leave Scale (ILS). Descriptive statistics, t-tests, ANOVA, Pearson correlation, and multiple regression analyses were used to test the research hypotheses. Results The findings show that job stress is significantly negatively correlated with job satisfaction and positively correlated with turnover intention. Interpersonal relationship stress emerged as the strongest predictor of turnover intention, while job autonomy stress significantly influenced job satisfaction. Demographic factors, including age, income, and education level, moderated these relationships, with younger, higher-income, and more educated employees reporting lower stress and higher satisfaction. Employees with dependents reported higher stress levels, lower job satisfaction, and greater turnover intentions compared to those without dependents. Conclusion This study underscores the importance of managing workplace stress and enhancing job satisfaction to reduce turnover intention, particularly during the COVID-19 pandemic. Interventions focused on improving interpersonal relationships and providing targeted support for older and lower-income employees are recommended to mitigate stress and improve retention rates.